Is inhibition of the renin-angiotensin system a new treatment option for Alzheimer's disease? - Kehoe, P; Wilcock, G (2007)
Findings from longitudinal and cross-sectional studies suggest an association between high blood pressure and dementia, and in turn the use of antihypertensives has been suggested to reduce incidence of dementia. Alzheimer's disease, the most common cause of dementia, is characterised in part by the deposition of amyloid beta protein (Abeta) in the brain. Reduction of Abeta load is now a major therapeutic strategy. In recent years the renin-angiotensin system, already of recognised importance in the pathogenesis of hypertension, has become a source of interest in the pathogenesis of Alzheimer's disease. This review explores molecular, genetic, and clinical studies that might help explain the relation between the renin-angiotensin system, hypertension, and Alzheimer's disease and whether treatment with angiotensin converting enzyme (ACE) inhibitors and similar treatment strategies have a part to play in the management of the disease.